Experience with academic detailing services for quality improvement in primary care practice. Issue 3 (24th May 2009) - May, F; Simpson, D; Hart, L; Rowett, D; Perrier, D
Abstract : Background: Despite longstanding experimental evidence about effectiveness of academic detailing, transitioning this research-based concept into acceptable primary care quality improvement services has been slow in the USA. The purpose of this study was to describe primary care uptake, retention and response to an academic-detailing-led service in the USA. Exploration of accessible performance indicators of service acceptance, and feasibility of use of an Australian academic detailing service model were secondary objectives. Methods: Over a 29-month period, an academic-detailing-led drug and therapeutics information service was offered to all primary care physicians providing ongoing patient care in Fayette County, Kentucky. Two programmes (on type 2 diabetes management and chronic pain management) incorporating up to four office visits were offered. Results: 102 of 130 (78%) eligible primary care physicians participated in the service, 72% receiving visits for the type 2 diabetes management programme, and 58% the chronic non-malignant pain programme. At all successive encounters, participants expressed a willingness to continue to receive visits. Difficulties were experienced in obtaining appointments for subsequent visits, although on direct enquiry, only one participant explicitly declined further visits. No notable differences existed between physicians accepting visits and those who did not. Across successive visits, passive indicators of satisfaction with the service included: duration of visits, office waiting times, retention of printed materials from one visit to the next, whether physicians wished their extender colleagues to also receive visits, and observed levels of interest and participation within encounters. Conclusions: Ongoing primary care quality improvement services spearheaded by academic detailing can be acceptable to US primary care physicians in practice.